2020
DOI: 10.3390/pathogens9110938
|View full text |Cite
|
Sign up to set email alerts
|

“Begging the Question”—Does Toxocara Infection/Exposure Associate with Multiple Sclerosis-Risk?

Abstract: Although the cause of multiple sclerosis (MS) is unclear, infectious agents, including some parasitic roundworms (nematodes), have been proposed as possible risk factors or contributors. Here, we conducted a systematic review and meta-analysis of published observational studies to evaluate whether there is a possible association between infection with, or exposure to, one or more members of the genus Toxocara (phylum Nematoda; superfamily Ascaridoidea) and MS. We undertook a search of public literature databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Although seroepidemiological studies suggest a relationship between Toxocara infection/exposure and epilepsy and other disorders, the pathogenic mechanisms underlying the neurological disorders are not well understood. One proposed mechanism relates to the migration of Toxocara larvae to, and through, the CNS [ 14 ], which may also account for other neuropsychiatric sequelae related to toxocariasis. Experimental studies in mice have revealed that Toxocara larvae can migrate in the tissues of the CNS for up to 28 days and survive for up to 2 years after infection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although seroepidemiological studies suggest a relationship between Toxocara infection/exposure and epilepsy and other disorders, the pathogenic mechanisms underlying the neurological disorders are not well understood. One proposed mechanism relates to the migration of Toxocara larvae to, and through, the CNS [ 14 ], which may also account for other neuropsychiatric sequelae related to toxocariasis. Experimental studies in mice have revealed that Toxocara larvae can migrate in the tissues of the CNS for up to 28 days and survive for up to 2 years after infection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI findings of neurotoxocariasis include subcortical, cortical or deep white-matter lesions with variable enhancement, which can associate with hydrocephalus, leptomeningeal or spinal cord involvement [ 13 ]. Findings from a range of epidemiological studies and meta-analyses [ 11 , 14 , 15 , 16 , 17 , 18 , 19 ] have indicated that Toxocara infection/exposure might play an under-appreciated role in inducing or contributing to neurological disorders, such as multiple sclerosis, schizophrenia, Parkinson’s, Alzheimer’s and/or epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Linked to the "hygiene hypothesis," it has been speculated that infection with particular microorganisms, particularly those occurring in childhood, may have a protective effect against allergic and autoimmune diseases. 10 In this regard, several studies have examined the possible involvement of infectious agents, such as Epstein-Barr virus and Toxocara spp., in promoting MS development, 8,[11][12][13] and others have suggested that parasites (e.g., Toxoplasma gondii, Necator americanus, and Trichuris suis) might prevent MS. [14][15][16] There is also been considerable debate as to whether Helicobacter pylori (H. pylori) is involved in development of MS or not. 17,18 H. pylori is a spiral-shaped, microaerophilic, gram-negative bacteria that colonizes the stomach of humans.…”
Section: Introductionmentioning
confidence: 99%
“…The wealth of literature published over recent decades requires critical systematic appraisals of information on NTDs. Taghipour et al [17] reviewed available medical literature to test a previous hypothesis of a possible association between Toxocara infection/exposure and multiple sclerosis (MS). Despite finding an association between anti-Toxocara IgG serum antibodies and MS in the published literature, the authors concluded that welldesigned and -controlled studies would be essential for a rigorous assessment of this association [17].…”
mentioning
confidence: 99%
“…Taghipour et al [17] reviewed available medical literature to test a previous hypothesis of a possible association between Toxocara infection/exposure and multiple sclerosis (MS). Despite finding an association between anti-Toxocara IgG serum antibodies and MS in the published literature, the authors concluded that welldesigned and -controlled studies would be essential for a rigorous assessment of this association [17]. On a distinct topic, focused on the evaluation of the function of a par-ticular molecule, Mughal et al [18] characterised the right open reading frame protein kinase (Sj-riok-1) gene and its gene product (Sj-RIOK-1) in Schistosoma japonicum (a human blood fluke).…”
mentioning
confidence: 99%